Exploring Elementary School Learning Models in Madura in Fostering Religious Moderation Literacy and Emotional Maturity - Tri Sutrisno; Nadi Suprapto; Neni Mariana; Wahono Widodo (Madrasah: Jurnal Pendidikan dan Pembelajaran Dasar, 2025)
This study aims to analyze the actual conditions of instructional practices, levels of religious moderation literacy, and emotional maturity among students of Madrasah Ibtidaiyah in Sumenep Regency. A mixed-methods approach was employed, integrating descriptive–exploratory qualitative methods with quantitative survey data. Data were collected through interviews, observations, questionnaires, and documentation across five Madrasah Ibtidaiyah representing both mainland and island regions. The findings indicate that learning practices in Sumenep have adopted the principles of Contextual Teaching and Learning (CTL) and local wisdom–based approaches; however, these practices remain predominantly focused on cognitive and socio-cultural aspects, with limited emphasis on the affective domain. This condition is reflected in the average scores of religious moderation literacy (2.41) and emotional maturity (2.57) on a four-point scale, suggesting that students’ understanding of tolerance and self-regulation is still largely conceptual and has not yet reached the stage of behavioral internalization. Madurese cultural values such as tengka’ (mutual respect) and bhâghus (politeness) demonstrate strong potential as reflective learning resources to strengthen students’ moderate character and emotional stability. These findings highlight the need for the development of an integrative learning model based on local wisdom that systematically integrates cognitive, affective, and social dimensions through stages of value orientation, exploration, collaborative learning, positive behavioral modeling, and reflective evaluation. Such a model is expected to foster a generation that is knowledgeable, empathetic, and characterized by moderate attitudes in accordance with the socio-cultural context of Sumenep. This study remains exploratory in nature and has not yet reached the effectiveness testing stage; therefore, further comprehensive research with more rigorous quantitative analysis is required.